2017
DOI: 10.1016/j.jvs.2016.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Benchtop quantification of gutter formation and compression of chimney stent grafts in relation to renal flow in chimney endovascular aneurysm repair and endovascular aneurysm sealing configurations

Abstract: This study showed that gutter volume was lowest in ch-EVAS in combination with a Viabahn CG. CG compression was lower in configurations with the Advanta V12 than with Viabahn. Renal flow is unrestricted by CG compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…Similarly, there have been no in vitro studies or clinical reports describing chimney deformation when devices are deployed in an adjacent fashion parallel to a primary endograft. In general, the D-ratios reported here follow trends reported elsewhere [15,27], namely: SE covered chimney grafts exhibit higher degrees of deformation compared to their BE counterparts. The distinctly unique findings of this study, however, are derived from the observed interactions of the adjacent self-expandable CGs deployed into the brachiocephalic trunk and left common carotid artery, as manifested by their varying lumen deformations ( Figure 7B).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, there have been no in vitro studies or clinical reports describing chimney deformation when devices are deployed in an adjacent fashion parallel to a primary endograft. In general, the D-ratios reported here follow trends reported elsewhere [15,27], namely: SE covered chimney grafts exhibit higher degrees of deformation compared to their BE counterparts. The distinctly unique findings of this study, however, are derived from the observed interactions of the adjacent self-expandable CGs deployed into the brachiocephalic trunk and left common carotid artery, as manifested by their varying lumen deformations ( Figure 7B).…”
Section: Discussionsupporting
confidence: 88%
“…Given the low sample size in this study, and uncontrolled implant positioning between groups, exact inferences could not be made. Nevertheless, these findings further support the notion that there exists an underlying structurefunction relation, primarily attributed to the native properties of nitinol [28], that may influence the optimal configuration of devices in chimney-type procedures [14,27].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Theoretically, chEVAS should be better than chEVAR because the compliant endobags fill the space between the Nellix stents and the chimney grafts, reducing the incidence of gutter type Ia endoleak. This advantage of chEVAS has been confirmed in bench models 15,16 and subsequently reported in clinical practice, most notably in the ASCEND Registry. 17 Logically, migration after chEVAS might occur less frequently and to a lesser degree compared to standard EVAS for several reasons.…”
Section: Introductionmentioning
confidence: 58%
“…The main advantage of this novel pump compared with other commercially available pumps is its simplicity in generating the peripheral flow profiles. Traditionally, two needle valves located at renal artery outlets, an air chamber and a needle valve in series located at the combined common iliac artery outlets representing a twoelement Windkessel were used 1,2,17,18 to simulate the vessel resistance and peripheral compliance in order to generate flow profile with reverse flow in the early diastolic phase. With the reciprocating roller pump design, it can produce back flow in the peripheral artery without the use of renal artery flow in the circuit, therefore it simplifies the flow circuit for in vitro studies involving infrarenal aorta, iliac, femoral, and other peripheral arteries.…”
Section: Discussionmentioning
confidence: 99%